“La naturaleza: laboratorio idóneo para la enseñanza aprendizaje de las ciencias naturales y su aplicación en los niños del 5to. año de educación general básica de la Unidad Educativa “Quito” del cantón Latacunga” - Casa Toctaguano, Edison Fabián (2022)
Education, the tool for changing society, daily seeks innovative mechanisms to improve teaching-learning processes. In this sense, relating nature and education will help teachers to break the traditional paradigms of face-to-face classes to generate practical learning, hence the proposal to promote the development of a practical guide for working in nature, which contributes both to teachers as students with means and resources. Likewise, it contributes to solving the problem of teaching and learning Natural Sciences, allowing us to relate the theoretical with the practical to get significant learning. The problem considered to carry out the research arises because the students feel unmotivated, the classes are monotonous and inactive, and not have participation of the students, resulting in traditional learning. The present research intends to fulfill the main objective of demonstrating that nature is the appropriate laboratory for the teaching and learning of Natural Sciences and to establish the specific aims which will guide the investigative process. The methodological design was focused on a qualitative and quantitative approach; observation, and interview techniques were used to collect information related to the research to establish the needs of the students. The obtained results allowed the elaboration of a practical guide that develops work activities in natural environments. Teachers must encourage creativity and innovation by using this natural laboratory as a pedagogical support instrument to motivate students to carry out the activities in this practical guide.